Športna vzgoja na Biotehniški fakulteti v Ljubljani s poudarkom na pohodništvu in jahanju - Janko, Gorazd (Šport (Ljubljana), 2019)
At the Biotechnical Faculty University in Ljubljana the sport programs Hiking and Riding have a special role. It is not a coincidence that the programs, which are carried out in nature, based on the nature of the study, are the most favorite among the students. If physical education was not an obligatory extra-curricular activity, sports teachers would not have the possibility to enthuse such a large amount of students about walking on mountains and riding horses. In both programs the emphasis is on active study and enjoyment of nature and preservation of it. The programs are attended by students of different study courses, different faculties and in doing so, socialize in a less formal way. Real connections are made between them, which grow into friendships and respect for diversity.
Keywords: Biotechnical Faculty; Biotehniška fakulteta; friendships; hiking; jahanje; obligatory extra-curricular activity; obvezna obštudijska dejavnost; physical education; pohodništvo; prijateljstvo; respect for diversity; riding; sport; spoštovanje različnosti; students; šport; športna vzgoja; študenti; University of Ljubljana; Univerza v Ljubljani